Ancient and pervasive expansion of adaptin-related vesicle coat machinery across Parabasalia - Maciejowski, William J; Gile, Gillian H; Jerlström-Hultqvist, Jon; Dacks, Joel B (International journal for parasitology, 2023)
The eukaryotic phylum Parabasalia is composed primarily of anaerobic, endobiotic organisms such as the veterinary parasite Tritrichomonas foetus and the human parasite Trichomonas vaginalis, the latter causing the most prevalent, non-viral, sexually transmitted disease world-wide. Although a parasitic lifestyle is generally associated with a reduction in cell biology, T. vaginalis provides a striking counter-example. The 2007 T. vaginalis genome paper reported a massive and selective expansion of encoded proteins involved in vesicle trafficking, particularly those implicated in the late secretory and endocytic systems. Chief amongst these were the hetero-tetrameric adaptor proteins or 'adaptins', with T. vaginalis encoding ∼3.5 times more such proteins than do humans. The provenance of such a complement, and how it relates to the transition from a free-living or endobiotic state to parasitism, remains unclear. In this study, we performed a comprehensive bioinformatic and molecular evolutionary investigation of the heterotetrameric cargo adaptor-derived coats, comparing the molecular complement and evolution of these proteins between T. vaginalis, T. foetus and the available diversity of endobiotic parabasalids. Notably, with the recent discovery of Anaeramoeba spp. as the free-living sister lineage to all parabasalids, we were able to delve back to time points earlier in the lineage's history than ever before. We found that, although T. vaginalis still encodes the most HTAC subunits amongst parabasalids, the duplications giving rise to the complement took place more deeply and at various stages across the lineage. While some duplications appear to have convergently shaped the parasitic lineages, the largest jump is in the transition from free-living to endobiotic lifestyle with both gains and losses shaping the encoded complement. This work details the evolution of a cellular system across an important lineage of parasites and provides insight into the evolutionary dynamics of an example of expansion of protein machinery, counter to the more common trends observed in many parasitic systems.
Keywords: Parasites; Trichomonas vaginalis; Animals; Tritrichomonas foetus; Parabasalidea; lidé; Computational Biology; paraziti; zvířata; výpočetní biologie; Metamonada; Clathrin; Evolutionary cell biology; Membrane trafficking; COPI; Humans